PENINGKATAN KOMPETENSI GURU DALAM PEMBELAJARAN BERBASIS MULTIMEDIA INTERAKTIF MELALUI IN HOUSE TRAINING DI SD NEGERI I GIRIWOYO - Karjani Karjani (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2020)
AbstractThe purpose of the School Action Research (PTS) is to determine the effect of In House Training on improving teacher competence in interactive multimedia-based learning. The method used in the School Action Research (PTS) with two cycles, each cycle consisting of stages (1) planning, (2) implementing corrective actions, (3) observation, and (4) reflection. Indicators of success in the School Actions Study if the activeness of the teachers, the competence of teachers operating interactive multimedia, and the competence of teachers in implementing multimedia-based learning shows 75%. The results of the School Action Research through In House Trainning have developed from Cycle 1 to Cycle 2 showing improvement. The results of the second cycle during the teacher participating in In House Trainning showed the activeness of the teacher that is 80%, the teacher's skills in operating multimedia 80% and the teacher's competence in implementing multimedia-based learning 86%. Based on the results of cycle 2 it can be concluded that there is an Increase in Teacher Competence in Multimedia-Based Learning through In House Training. Based on these results it is expected that (1) Giriwoyo Elementary School I teachers in order to optimize their role as interactive multimedia-based planners, organizers, and learning (2) School principals facilitate teachers to improve interactive multimedia-based learning competencies. (3) School Committee I Giriwoyo Elementary School I facilitates interactive multimedia facilities and funds In House Training activities.Keywords: Teacher competence, interactive multimedia, In House Training.